Nobody's gonna slow me down? The effects of a transportation cost shock on firm performance and behavior - Catarina Branco; Dirk C. Dohse; Jo\~ao Pereira dos Santos; José Tavares (Journal of Urban Economics, 2023)
We study the firm-level responses to a substantial increase in transportation costs in the wake of a quasi-experiment that introduced tolls in a subset of Portuguese highways. Exploiting a unique dataset encompassing the universe of Portuguese private firms, we find that the introduction of tolls caused a substantial decrease in turnover (-10.2%) and productivity (-4.3%) in treated firms vis-à-vis firms in the comparison group. In response to the tolls, firms substantially cut employment-related expenses and purchases of other inputs. Labor costs were reduced by both employment cuts and a decrease in average wages. While firms did not increase inventory, there is some evidence for increased firm exit, in particular by firms in tradables sectors.
Keywords: R48; L25; R12; 330; Road tolls; Infrastructure; Firm performance; Firm behavior; Location; Portugal